Linear precoder design for correlated rician fading channel under imperfect CSI - Priya, S. B. M. (China communications, 2023)
In this paper, we have modeled a linear precoder for indoor multiuser multiple input multiple output (MU-MIMO) system with imperfect channel state information (CSI) at transmitter. The Rician channel is presumed to be mutually coupled and spatially, temporarily correlated. The imperfection with CSI is primarily due to the channel estimation error at receiver and feedback delay amidst the receiver and transmitter in CSI transmission. Along with, the insufficient spacing between the antenna at transmitter and receiver persuades mutual coupling (MC) among the array elements. In addition, the MIMO channel is presumed to be jointly correlated (Weichselberger correlation model). When we look back on the existing precoder design, it considered spatial correlation alone disregarding joint correlation of antenna array elements. With all above assumption, we have designed a linear precoder which minimizes mean squared error (MSE) subjected to total transmit power constraint for MU-MIMO system. The simulation results proven that proposed precoder shows substantial enhancement in bit error rate (BER) performance in comparison with the existing technique. The mathematical analysis corroborates the simulation results.